Extracellular Water and Blood Pressure in Adults with Growth Hormone (GH) Deficiency: A Genotype-Phenotype Association Study - Barbosa, Edna J. L. (Public Library of Science, 2014)
OBJECTIVES: Growth hormone deficiency (GHD) in adults is associated with decreased extracellular water volume (ECW). In response to GH replacement therapy (GHRT), ECW increases and blood pressure (BP) reduces or remains unchanged. Our primary aim was to study the association between polymorphisms in genes related to renal tubular function with ECW and BP before and 1 year after GHRT. The ECW measures using bioimpedance analysis (BIA) and bioimpedance spectroscopy (BIS) were validated against a reference method, the sodium bromide dilution method (Br(−)). DESIGN AND METHODS: Using a candidate gene approach, fifteen single-nucleotide polymorphisms (SNPs) in nine genes with known impact on renal tubular function (AGT, SCNN1A, SCNN1G, SLC12A1, SLC12A3, KCNJ1, STK39, WNK1 and CASR) were genotyped and analyzed for associations with ECW and BP at baseline and with their changes after 1 year of GHRT in 311 adult GHD patients. ECW was measured with the Br(−), BIA, and BIS. RESULTS: Both BIA and BIS measurements demonstrated similar ECW results as the reference method. At baseline, after adjustment for sex and BMI, SNP rs2291340 in the SLC12A1 gene was associated with ECW volume in GHD patients (p = 0.039). None of the SNPs influenced the ECW response to GHRT. One SNP in the SLC12A3 gene (rs11643718; p = 0.024) and three SNPs in the SCNN1G gene [rs5723 (p = 0.02), rs5729 (p = 0.016) and rs13331086 (p = 0.035)] were associated with the inter-individual differences in BP levels at baseline. A polymorphism in the calcium-sensing receptor (CASR) gene (rs1965357) was associated with changes in systolic BP after GHRT (p = 0.036). None of these associations remained statistically significant when corrected for multiple testing. CONCLUSION: The BIA and BIS are as accurate as Br(−) to measure ECW in GHD adults before and during GHRT. Our study provides the first evidence that individual polymorphisms may have clinically relevant effects on ECW and BP in GHD adults.